Membangun Perilaku Pembelian Bisnis Franchise Ayam Crispy Di Tegal Melalui Saluran Distribusi, Harga Dan Kualitas Produk - Wiyanti, Sari; Tresna Pamungkas, Bisma Reza; Alimudin, Toat Nur; Maulana, M. Arif; Ichsan, Achmad Faqihul (Fakultas Ekonomi - Universitas Setia Budi, 2023)
The cripy chicken franchise business in Tegal City is a business opportunity for beginners and does not have a high risk. This business product is very popular with people of all walks of life and all ages. The purpose of this study was to analyze the buying behavior of the crispy chicken franchise business in the city of Tegal. This type of research is quantitative research, with a population of crispy chicken franchise traders in Tegal City. The sampling technique used is non-probability sampling and the sampling method is accidental sampling. The results of the research based on the distribution channel t test obtained the tcount value, namely -0.185 <1.661 with a sig. 0.853 > 0.05 means that H0 is accepted and H1 is rejected. The price obtained by tcount is 3,490 > 1.661 with a sig. 0.001 <0.05 means that H0 is rejected and H2 is accepted. Product Quality, namely 1,886 > 1,661 with a sig. 0.043 <0.05 means that H0 is rejected and H3 is accepted. The results of the F test obtained fcount > ftable, namely 27,578 > 2.467 with a sig. is 0.00 in other words the sig. < 0.05 or 0.000 < 0.05, means that H0 is rejected. Based on the results of the F test, then H4 is accepted, it is concluded that there is influence of Distribution Channels, Prices, and Product Quality together simultaneously influence the Buying Behavior of Crispy Chicken Franchise Business in Tegal City.